PEMAKAIAN EUFEMISME DALAM SURAT KABAR SOLOPOS - Fifit Puspitasari; Sumarwati Sumarwati; Edy Suryanto (Universitas Sebelas Maret, 2019)
There are many strategies in the use of language for specific purposes by euphemisms and it found also in the newspaper Solopos primarily on the topic of politics. The purpose of this study is to describe and explain: (1) the form of the use of euphemisms in the daily newspaper Solopos Edition April 2018, (2) the function of the use of euphemisms in the news daily newspaper Solopos Edition April 2018, (3) its relevance text learning material against anecdote at the high school. This research is qualitative research with the source data comes from the text of the news on the news in the newspaper Solopos. This research uses sampling purposive sampling and analysis techniques using a flowing or flow model of analyzing in analyzing the data. The results of this research are (1) Found 8 forms a euphemism that is, a euphemism in the form of loan words, euphemism be unfamiliar terms, a euphemism in the form of metaphor, euphemism be figurative expressions, euphemisms in the form of an acronym, abbreviation, in the form of euphemism in the form of one word for another word, and euphemisms in the form of paraphrasing; (2) the function of the use of euphemisms in the daily newspaper Solopos April 2018 is for politeness, obscure meaning, not to offend or cause conflict, reducing shame, mentioning the title of education, mentioning religious terms, and to keep secret things.